In Vitro Study on Influence of Implant Placement Angulation on Biomechanical Stability - Vinay K. M. Bhairammanavar; Ngangbam J. Singh; K. Anusha Ravindra; Sanjana N. Kyatam; Shrinidhi Jain; Krishna Gorde (Journal of Pharmacy and Bioallied Sciences)
Background: Dental implant placement angulation plays a critical role in ensuring biomechanical stability, which directly affects the success of prosthetic rehabilitation. Misaligned implants can lead to uneven stress distribution, jeopardizing long-term stability and osseointegration. This in vitro study aimed to evaluate the influence of implant angulation on the biomechanical stability of dental implants under controlled laboratory conditions. Materials and Methods: A total of 60 dental implants (4.2 mm × 10 mm) were inserted into polyurethane blocks simulating bone density (D2 type). Implants were divided into three groups based on angulation: Group A (0°; n = 20), Group B (15°; n = 20), and Group C (30°; n = 20). A universal testing machine was used to measure insertion torque values (ITV) and implant stability quotient (ISQ) scores immediately post-placement. A load-to-failure test was performed to assess the maximum load-bearing capacity. Data were statistically analyzed using ANOVA with significance set at P < 0.05. Results: The insertion torque values decreased with increase in angulation: Group A (0°) recorded an average ITV of 45 ± 3 Ncm, Group B (15°) showed 35 ± 4 Ncm, and Group C (30°) exhibited 27 ± 5 Ncm. Implant stability quotient (ISQ) scores followed a similar trend: Group A (72 ± 2), Group B (65 ± 3), and Group C (58 ± 4). Load-to-failure testing revealed significantly higher stability in Group A (1,200 ± 50 N) compared to Group B (950 ± 40 N) and Group C (750 ± 30 N) (P < 0.05). Conclusion: Increasing implant angulation negatively impacts biomechanical stability by reducing insertion torque, ISQ values, and load-bearing capacity. Optimal placement at a 0° angle provides superior mechanical stability and should be prioritized in clinical settings to enhance implant longevity.